The Impact of Teaching Practice on the Development of Teaching Skills among Student Teachers at Zawia Faculty of Education (Comprehensive Journal of Science, 2025)
This study sets out to investigate the importance of Teaching Practice stage on developing teaching skills. It also, toidentify which teaching skills are most developed during the practicum and the challenges they encounter in implementingTeaching Practice.The data of the study was collected through 30 student teachers who are in the practicum experience at Zawia Faculty ofEducation who were performing teaching practicum during their final semester in public schools. The results of this studyindicated that trained teachers are better than untrained and the participants held positive perspectives regarding theimportance of Teaching Practice in enhancing their teaching skills.It was recommended that teacher-training courses for teachers should be achieved and student teachers should beencouraged to undergo professional teaching courses and use variety of teaching methods.